Penerapan Pembelajaran SAINS di Era Digital:Microsite Berbasis Deep Learning dan TPACK pada Materi Penegenalan Panca Indera untuk Siswa SD Kelas IV - Dhuwi Noviyanti; Hidayah Indah Paramesthi; Luthfiana Permata Bunda; Mayla Fara Azzahra; Nanda Lina Oryza Septiviana; Nazwa Nur Fadhila; Oktaviana Eka Rahmadani; Liss Dyah Dewi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Science learning in elementary schools needs to be designed contextually so that students understand the five senses from an early age, with the aim of health education. Teaching modules are developed with five senses material through a Technological Pedagogical Content Knowledge (TPACK) approach. This module provides an understanding of the five senses (Content Knowledge) with a pedagogical strategy based on Problem Based Learning (Pedagogical Knowledge) applied to encourage sensory exploration in students' learning experiences.The five senses teaching aids which include visualization of the eyes, nose, tongue, ears, and skin, are expected to improve students' understanding of the material being taught. Then, the use of technology such as learning videos and digital evaluation (Technological Knowledge) increases student involvement in understanding the importance of maintaining health from an early age. This study uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The trial was conducted in 4th grade elementary school involving teachers and students. The results showed that this module was effective in improving students' understanding of the concept of the five senses and their awareness of the importance of maintaining their sense organs. The integration of TPACK in the module allows students to gain a deeper learning experience through the use of technology as an aid. Thus, this module becomes an alternative in learning science and increases learning effectiveness through an optimal combination of content, educational materials, and technology.